Key Factors in Improving the Maturity of Information Technology Governance: A Case Study of State-owned Enterprise in Indonesia - Rokhman Fauzi; Rahmat Mulyana (International Journal of Innovation in Enterprise System, 2020)
The assessment of IT governance maturity is part of the assurance function. The assessment iscarried out to ensure technology support in achieving business goals. In this context, companiesshould comply with regulations, as well as the need to continue to improve the quality ofimplementation of IT governance. The average value of PT X's IT governance maturity in Year2 has increased from 3.21 to 3.26. There is an increase in the average score of 0.05 over oneyear. Success factors in implementing IT governance must be maintained and encouraged tocontinue the grow. This research was conducted to identify what organizational initiatives toincrease the maturity and what the key factors are. Factors identification is done using evidenceanalysis method based on CSF references and attributes criteria. The results of the analysisobtained key factors that strengthen the maturity. The main factors are CSF2 providing ITinfrastructure that supports the development and exchange of IT applications and services(21.72%), and CSF4 staff development to meet professional IT HR qualifications (17.39%). Onthe other hand, maturity attribute which gave the biggest contribution was ATR1 related topolicies and procedures (34.6%), and ATR3 related to defining goals and actions (30.77%).